Role of Social Media in Tourism and its Use by NGO’s: Preliminary Case Study on Bodrum, Turkey - Özcan, Ezgi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
The purpose of this study; Bodrum’s destination properties, strengths and weaknesses, social media and tourism relations, social media and marketing extensions and to determine where it is in the field of publicity and marketing of this city which is a tourism paradise; Unions, associations and foundations in this direction. Also this study examines; destination image and attitudes toward social media. The narrow area of the work was formed by associations and non-governmental organizations in Bodrum city. In the study Bodrum was evaluated as a strong potential in terms of tourism at the same time weak cognitive features such as politics, external influences, economics, security are also discussed. By conducting interviews with associations, associations and associations, the effectiveness of the social media, which has become the only agenda of the age, has been investigated as well. In addition, when working hypotheses were tested, the data were combined using different methods. Results of the study; The institutions that play a role in creating the Bodrum image at the country level, the tourism sector employees and the social media users, while the academic area has achieved results that will shed light on destination features and work towards tourism image. With the development and widespread use of technology, the rate of Internet use in our country and in the world is rapidly increasing and also consumers are also affected by the marketing of goods and services. In terms of Internet usage and social media tourism operations, it also emerges as an extremely important tool in tourism product preference. Therefore, it is necessary to examine the role of social media in tourism product preference and to evaluate these platforms ethically.

ÖZ: Çalışma; Bodrum’un destinasyon özelliklerini, güçlü ve zayıf özelliklerini, sosyal medya ve turizm ilişkisini, sosyal medya ve pazarlamanın uzantılarını ve bir turizm cenneti olan bu kentin tanıtım ve pazarlama alanında nerede olduğunu belirlemeyi; birlik, dernek ve vakıfların bu yöndeki çalışmalarını incelemeyi amaçlamıştır. Ayrıca çalışma; destinasyon imajı ve sosyal medyaya olan tutumları ölçen kavramsal modeli önermeyi amaçlamıştır. Çalışmanın dar alanını Bodrum kentindeki dernekler ve sivil toplum kuruluşlarından oluşturmuştur. Çalışmada Bodrum’un turizm anlamındaki güçlü potansiyeli değerlendirilirken politika, dış etkiler, ekonomi, güvenlik gibi zayıf bilişsel özellikler de ele alınmıştır. Vakıf, dernek ve birliklerle röportajlar yapılarak, çağın tek gündemi haline gelen sosyal medyanın etkinliği araştırılmıştır. Ayrıca çalışma hipotezlerinin test edilmesinde farklı yöntemler kullanılarak veriler bir araya getirilmiştir. Çalışmanın sonuçları; ülke düzeyinde Bodrum imajının oluşturulmasında rol oynayan kurumlara, turizm sektörü çalışanları ve sosyal medya kullanıcıları kişilere, akademik alanda ise destinasyon özellikleri ve turizm imajına yönelik çalışmalara ışık tutacak nitelikte sonuçlara ulaşılmıştır. Teknolojinin gelişmesi ve yaygınlaşması ile birlikte ülkemizde ve dünyada internet kullanım oranı büyük bir hızla artmaktadır ve ayrıca tüketicilerin de mal ve hizmet alımlarında pazarlamanın bu yeni pazarlama kanalından etkilendikleri görülmektedir. İnternet kullanımı ve sosyal medya turizm işletmeleri açısından da turistik ürün tercihinde son derece önemli bir araç olarak ortaya çıkmaktadır.
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2017. Supervisor: Assist. Prof. Dr. Rüçhan Kayaman.
Keywords: Tourism; Tourism--Marketing--Social media--Internet marketing--Bodrum (Turkey); Hospitality industry--Marketing; Tourism--Marketing; Social Media; Online Travel Information; Sustainable Tuorism; NGO’s Role; Destination Image; Destination Attributes; Bodrum